PENATAAN FISIK PULAU PAHAWANG SEBAGAI AREA PENDUKUNG KEGIATAN WISATA BAHARI - Faisal Radhiansyah; I G Oka Sindhu Pribadi (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The management of coastal areas makes a major contribution to the regional economy. The development of maritime-based tourism in Lampung Province is carried out through tourism activities on Pahawang Island which has abundant natural tourism potential, such as mangrove forests, white sand, and the underwater world. In order to develop the tourism areas, one thing that needs to be considered is maintaining the existing natural ecosystem, especially in Dusun  Jeralangan which is starting to run out of innovation in developing the tourism activities. The purpose of this research is to look at the existing condition of the Pahawang Island Tourism Area, to compare and benchmark similar tourism areas and to propose the concept of physical arrangement and facilities that will be conceptualized in the master plan to increase the attractiveness of the area. This study used descriptive analysis to elaborate the results of the analysis carried out. The results of the study indicate that there are still facilities that need to be developed both in terms of supporting aspects of accessibility, public facilities, telecommunications, clean water, and health facilities. This is evidenced by the preferences of visitors seen from the customer satisfaction index value of 43% indicating that visitors and the public are not satisfied with several aspects of Pahawang Island. Based on this, the concept and arrangement plan is carried out by taking into account the projection needs until 2025. The supporting aspects that need to be developed in the Pahawang Island Tourism Area need to be carried out in order to support existing marine tourism activities. Keywords:  Tourism; Marine tourism; Lampung province; Physical Arrangement; Importance Performance Analysis Abstrak Pengelolaan wilayah pesisir memberikan kontribusi besar terhadap perkenomian wilayah. Pengembangan pariwisata berbasis bahari di Provinsi Lampung dilakukan melalui kegiatan wisata di Pulau Pahawang yang memiliki potensi wisata alam melimpah yaitu hutan bakau, pasir putih, dan dunia bawah laut. Pengembangannya perlu di perhatikan untuk teteap menjaga ekosistem alam yang ada khususnya pada Dusun Jeralangan yang mulai kehabisan inovasi dalam mengembangkan wisata. Tujuan dari penelitian ini adalah melihat kondisi eksisting Kawasan Wisata Pulau Pahawang, melakukan perbandingan benchmarking dengan wisata serupa, serta mengusulkan konsep penataan fisik dan sarana yang dituangkan kedalam masterplan guna meningkatkan daya tarik Kawasan. Penelitian ini menggunakan analisis deskriptif untuk mengelaborasi hasil analisis yang dilakukan. Hasil dari penelitian menunjukkan bahwa masih terdapat kondisi fasilitas yang perlu dilakukan pengembangan baik dari aspek pendukung aksesibilitas, fasilitas umum, telekomunikasi, air bersih, dan sarana kesehatan. Hal ini dibuktikan dengan preferensi pengunjung dilihat dari nilai costumersatisfaction index sebesar 43% mengindikasi pengunjung dan masyarakat kurang puas pada beberapa aspek di Pulau Pahawang. Berdasarkan hal tersebut, dilakukan konsep dan rencana penataan dengan memperhatikan kebutuhan proyeksi sampai tahun 2025. Aspek pendukung yang perlu di kembangkan di Kawasan Wisata Pulau Pahawang perlu untuk dilakukan dalam rangka menunjang kegiatan wisata bahari yang ada.